تأثير تكنولوجيا الكرتون على سلوك الطفل قبل التمدرس الدراسة الميدانية في المدينة البيضاء - حليمة كشنة; جهيدة شريكي; دلاسي محمد (My University)
Our study aimed to identify the impact of cartoon technology on the child's behavior before school, so that we relied on the descriptive approach and our use of the questionnaire tool and indirect observation to collect information and data. We divided the questionnaire tool into 04 main axes The first axis is dealing with the mother's personal data The second axis is dealing with the attitude of mothers about their children's interest in cartoons The third axis is addressing the nature of the behaviors that your child acquires by watching cartoons The fourth axis is the nature of the values that your child acquires as a result of watching cartoons. Keywords: child, family, technology, human behavior, media